Insula tuning towards external eating versus interoceptive input in adolescents with overweight and obesity. (1st October 2015) - Mata, Fernanda; Verdejo-Roman, Juan; Soriano-Mas, Carles; Verdejo-Garcia, Antonio
Highlights: Insula activation negatively correlates with interoceptive sensitivity in obesity. Insula activation positively correlates with external eating in obesity. Caudate activation positively correlates with external eating in obesity. In obesity, the interoceptive brain system is not tuned towards bodily feedback. Abstract: This study was aimed to examine if adolescent obesity is associated with alterations of insula function as indexed by differential correlations between insula activation and perception of interoceptive feedback versus external food cues. We hypothesized that, in healthy weight adolescents, insula activation will positively correlate with interoceptive sensitivity, whereas in excess weight adolescents, insula activation will positively correlate with sensitivity towards external cues. Fifty-four adolescents (age range 12–18), classified in two groups as a function of BMI, excess weight (n = 22) and healthy weight (n = 32), performed the Risky-Gains task (sensitive to insula function) inside an fMRI scanner, and completed the heartbeat perception task (measuring interoceptive sensitivity) and the Dutch Eating Behaviour Questionnaire (measuring external eating as well as emotional eating and restraint) outside the scanner. We found that insula activation during the Risky-Gains task positively correlated with interoceptive sensitivity and negatively correlated with external eating in healthy weight adolescents. Conversely, in excess weight adolescents, insula activation positively correlated with external eating and negatively correlated with interoceptive sensitivity, arguably reflecting obesity related neurocognitive adaptations. In excess weight adolescents, external eating was also positively associated with caudate nucleus activation, and restrained eating was negatively associated with insula activation. Our findings suggest that adolescent obesity is associated with disrupted tuning of the insula system towards interoceptive input.